Integrasi Dinamis Pasar Modal Indonesia dengan Pasar Modal International pada Masa Pandemi Covid-19 - Stefany Cindy Sugiyanto; Robiyanto Robiyanto (AFRE (Accounting and Financial Review), 2020)
The Covid-19 pandemic has an impact on the world economy especially on the stock mar-ket, thus the aim of this study is to determine whether there is dynamic integration be-tween the stock markets in Indonesia with the capital market in Asia and in the world during Covid-19 pandemic. This study uses return data from the closing price of 12 stock indices, namely ASX, DOWJONES, FTSE, HANGSENG, IHSG, KLSE, KOSPI, NIK-KEI, PSEI, SET, STI, and TAIWAN from January to December 2020 that have been ana-lyzed using DCC-GARCH. The results showed that the stock markets of both Indonesia, Asia and the world were dynamically integrated due to the global crisis of the Covid-19 pandemic. The results showed that there was a contagion effect on the stock market that occurred during the period when the Covid-19 pandemic crisis occurred. This research can be a reference for investors who want to invest in stocks in Indonesia during the Covid-19 pandemic. DOI: https://doi.org/10.26905/afr.v3i2.551